No evidence for an Eddington-ratio dependence of X-ray weakness in BALQSOs. Issue 4 (6th July 2018) - Vito, F; Brandt, W N; Luo, B; Shemmer, O; Vignali, C; Gilli, R
ABSTRACT: Several works have studied the relation between X-ray, ultraviolet (UV), and wind properties in broad absorption line quasars (BALQSOs), generally concluding that the formation of strong winds is tightly connected with the suppression of the ionizing extreme ultraviolet (EUV)/X-ray emission. The Eddington ratio (λEdd ), which measures the accretion rate, is also known to be related with outflow and emission-line properties in the general quasar population. Moreover, models describing quasar accretion depend on λEdd, which can thus possibly affect the relative production of accelerating UV and ionizing EUV/X-ray radiation. In this work, for the first time, we investigated whether BALQSO X-ray properties are related with the Eddington ratio. We selected a sample of 30 BALQSOs with accurate measurements of black-hole mass and BAL properties from the literature, and we complemented it with four additional BALQSOs we observed with XMM–Newton to populate the low and high Eddington-ratio regimes. We did not find evidence for a strong relation between λEdd and X-ray suppression, which however shows a significant correlation with the strength of the UV absorption features. These findings are confirmed also by considering a sample of mini-BALQSOs collected from the literature.